2019
DOI: 10.17826/cumj.569533
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine among couples receiving infertility treatment

Abstract: The aim of this study was to determine the use of complementary and alternative medicine methods in women and men receiving infertility treatment and the factors affecting them. Materials and Methods: This cross-sectional study was conducted in infertility centre of a training and research hospital. The study included 150 infertile women who received infertility treatment for at least one month and willing to participate in the study. Data were collected by ''Data Collection Form'' which created by researchers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Another study with infertile women showed that the majority of women who used supportive therapy learned these methods from their families, relatives and friends (51,4%), while very few people used them on the recommendation of a doctor (2.2%), but the relationship with their level of education is not known (11). Another study did not find a relationship between the method of use of supportive therapy and the level of education (12). However, another study found that women with low levels of education often use supportive therapy methods more often (13).…”
Section: The Effect Of Educational Level In Accessing Information Abomentioning
confidence: 96%
“…Another study with infertile women showed that the majority of women who used supportive therapy learned these methods from their families, relatives and friends (51,4%), while very few people used them on the recommendation of a doctor (2.2%), but the relationship with their level of education is not known (11). Another study did not find a relationship between the method of use of supportive therapy and the level of education (12). However, another study found that women with low levels of education often use supportive therapy methods more often (13).…”
Section: The Effect Of Educational Level In Accessing Information Abomentioning
confidence: 96%